Asuhan Keperawatan Pada Pasien Dengan Hipertensi di Ruang Muzdalifah RS ‘Aisyiyah Kota Pariaman - Mifthahul Arifah; Kheniva Diah Anggita; Mike Asmaria; Aulia Asman (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is often called the “silent killer” because it frequently causes no symptoms, yet poses a risk of serious complications such as heart disease, kidney failure, diabetes mellitus, and stroke. Globally, approximately 33% of adults aged 30–79 have hypertension. In Indonesia, the prevalence reaches 30.8%, in West Sumatra 24.1%, and in Pariaman City, there are 8,599 recorded cases of hypertension. Data from ‘Aisyiyah Hospital in Pariaman City for the year 2025 indicates 140 cases of hypertension. This study aims to provide nursing care for a patient with hypertension through the stages of assessment, diagnosis, intervention, implementation, and evaluation. The study was conducted in the Muzdalifah Ward of ‘Aisyiyah Hospital in Pariaman from February 10–14, 2026, on one patient, Mrs. E, using observation, interviews, physical examination, and a review of medical records. The study identified five nursing problems: risk of ineffective cerebral perfusion, risk of electrolyte imbalance, nutritional deficit, acute pain, and sleep pattern disturbance. Interventions included vital sign monitoring, medication administration, electrolyte monitoring, electrolyte management, pain management, and sleep support. After five days of nursing care, blood pressure improved, electrolyte levels increased, pain decreased, appetite increased, and sleep patterns improved. Comprehensive and continuous nursing care effectively improved the condition of patients with hypertension.